Pengaruh Kepemimpinan, Motivasi Kerja, Pelatihan Dan Reward Kepuasan Karyawan Studi Kasus PT.AKM (Antar Kerja Mandiri) Metro - Rozaki, Muhammad Saifur; Dupri, Muhammad Demsi (Universitas Muhammadiyah Metro, 2022)
This study aims to determine the effect of leadership, work motivation, training, and giving rewards on employee satisfaction. The type of research used in this study is quantitative. The object of this research is PT. ATM (Between the Power Independent) Metro, population as much as 40 respondent Data collection techniques using observation, interviews and questionnaires Data analysis techniques using SPSS 22 include test instrument requirements test requirements analysis, hypothesis testing. Based on the results of the study indicate that the variables of leadership, work motivation, training and giving rewards have a significant and significant effect on employee satisfaction, work motivation variable and significant effect on employee performance, training variable and significant effect on employee performance, and the variable giving of rewards has a significant and significant effect on employee satisfaction. Meanwhile, the simultaneous test of leadership, work motivation, leadership style and giving of rewards has a significant and significant effect on employee performance. Keywords : leadership, work motivation, training and giving rewards to employee satisfaction.